Roman Army Papers - Gilliam, J.F., (Classical Studies - Book Archive pre-2000., 1986)
The forty-four papers, with addenda and indices, written between 1940 and 1985 embody a lifetime's work by this eminent Princeton scholar, noted for his deft handling of the inscriptions and papyri on which our knowledge of the Roman army rests.